Rekonstruksi Pamali sebagai Jarimah Ta’zir: Analisis Fiqh al-Bi’ah dalam Preservasi Leuweung Larangan - Irfan Fauzi; Arini Nabila Azzahra (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
State-based conservation in Indonesia often faces institutional failure and social resistance, resulting in continued deforestation. Conversely, Indigenous conservation models in West Java, specifically the Leuweung Larangan (forbidden forest), demonstrate significant ecological resilience. However, the legal standing of these customary practices within Islamic jurisprudence remains under-theorized, creating a dichotomy between Adat (custom) and Sharia. This study proposes a juridical reconstruction of the Sundanese taboo mechanism (Pamali) as Jarimah Ta’zir (discretionary sanction) to strengthen environmental law enforcement. Utilizing a socio-legal approach and ecological hermeneutics, this research analyzes Yusuf al-Qardhawi’s concept of Fiqh al-Bi’ah and Seyyed Hossein Nasr’s sacred science, alongside relevant empirical data on Indigenous forest governance. The findings demonstrate that Leuweung Larangan structurally manifests as Hima Syar’i (sacred protected zone). Operationally, Pamali functions not merely as a cultural myth, but as a preventive legal instrument (Sadd al-Dzari’ah) where environmental violations constitute religious criminal acts. This creates a